2003
DOI: 10.1007/s00122-002-1174-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species amplification of mitochondrial DNA sequence-tagged-site markers in conifers: the nature of polymorphism and variation within and among species in Picea

Abstract: Primers previously developed to amplify specific non-coding regions of the mitochondrial genome in Angiosperms, and new primers for additional non-coding mtDNA regions, were tested for their ability to direct DNA amplification in 12 conifer taxa and to detect sequence-tagged-site (STS) polymorphisms within and among eight species in Picea. Out of 12 primer pairs, nine were successful at amplifying mtDNA in most of the taxa surveyed. In conifers, indels and substitutions were observed for several loci, allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 53 publications
(80 reference statements)
3
67
0
Order By: Relevance
“…Nevertheless, their application in a single taxonomic unit, as in Larix species, was not completely successful. Jaramillo- Correa et al (2003) have also observed difficulties for applying universal mitochondrial primers in gymnosperms.…”
Section: Polymorphisms Of Parental Speciesmentioning
confidence: 97%
“…Nevertheless, their application in a single taxonomic unit, as in Larix species, was not completely successful. Jaramillo- Correa et al (2003) have also observed difficulties for applying universal mitochondrial primers in gymnosperms.…”
Section: Polymorphisms Of Parental Speciesmentioning
confidence: 97%
“…In most conifers including Larix, the chloroplast genome is paternally inherited, whereas the mitochondrial genome is maternally inherited (Szmidt et al 1987;Mogensen 1996;Whittle and Johnson 2002;Jaramillo-Correa et al 2003). Five mtDNA introns [cox1-intron1 (Lu et al 1998), matR-intron1 (Qiu et al 1999), nad1-intron b/c , nad3-intron1 (Soranzo et al 1999), and nad5-intron1 Table 4), and 1.0 U of Platinum Taq DNA polymerase (Invitrogen).…”
Section: Markers Of Nuclear Gene Sequencesmentioning
confidence: 99%
“…Notably, ITS sequences have been extensively used to determine genetic diversity and to classify several plants species because they are highly variable 5,6 . Besides the ITS sequences, organelle DNA, chloroplast DNA (cpDNA) and mitochondrial DNA (mtDNA), are the other targets of genetic diversity and classification studies due to their maternal inheritance, smaller-sized molecule compared to genomic DNA, and low level of recombination, which make them easier and more reliable to examine the phylogenetic applications 7,8 . The rDNA-ITS or organelle DNAs has been widely used for the above-mentioned applications not only by sequences analysis but also by comparison of their PCR-amplified fragments.…”
Section: Introductionmentioning
confidence: 99%